Polemik Periwayatan Hadis bil Ma’na: Studi Komparasi Pemikiran Syuhudi Ismail dan Mahmud Abu Rayyah - Hadiana, Shinta Nuriyah; Muhid, Muhid (Fakultas Ushuluddin UIN Sunan Gunung Djati Bandung, 2024)
The narration of the hadith bil ma’na is a topic that gives rise to debate and differences of opinion among Muslim scholars and scholars. Some controversy has arisen regarding caution in interpreting the meaning of hadith outside the text, fearing that this could open the door to subjective interpretations or deviations from the original teachings. There are several figures who have an influence on the study of hadith, especially regarding the narration of bi al-ma'na, one of which is interesting to study is Syuhudi Ismail and Mahmud Abu Rayyah in understanding the narration of Hadith bi al-ma'na. This research aims to find out how Syuhudi Ismail and Mahmud Abu Rayyah think regarding the polemic of the narration of the hadith bi Al-Ma'na, then compare the thoughts of the two figures to find similarities and differences in their thoughts regarding the narration of the hadith bi al-ma'na. This research uses a qualitative approach with a review of literature studies. The research results show that Syuhudi Ismail tends to be more flexible in accepting the narration of the bil ma’na hadith, provided that the core meaning of the hadith is maintained. On the other hand, Mahmud Abu Rayyah showed a more cautious approach and tended not to allow the narration of bi al-ma'na, because he was worried about the possibility of changing the original meaning. Although both aim to maintain the validity of the meaning of the hadith.